Anharmonicity driven unusual particle-to-wave-like phonon crossover leads to ultralow thermal conductivity in Tl 2 AgI 3 - Riddhimoy Pathak; Sayan Paul; Shuva Biswas; Swapan K. Pati; Kanishka Biswas (Proceedings of the National Academy of Sciences, 2026)
Realization of unusual particle-to-wave-like crossover in phonon transport and understanding its fundamental structural origin can guide the design of materials with ultralow thermal conductivity. Here, we report such a crossover from particle-like phonon propagation to wave-like coherence with increasing temperature in the zero-dimensional (0D) metal halide, Tl 2 AgI 3 . Composed of discrete (Tl 6 I) 5+ and (Ag 3 I 8 ) 5− subunits, the structure exhibits intrinsic lattice instability governed by Pauling’s third rule where face-sharing of polyhedra drives Coulombic cationic repulsion causing local distortion of Ag atoms, as confirmed by synchrotron X-ray pair distribution function (X-PDF) analysis and ab initio molecular dynamics (AIMD) simulations. Anharmonic low-energy rattling of Tl is evidenced within the (Tl 6 I) 5+ framework. These structural disorders generate low-frequency localized and anharmonic optical phonons that hybridize with acoustic branches, strongly suppressing lattice thermal conductivity ( κ l ). Consequently, κ l drops to ~0.18 W/m.K at 125 K and remains nearly temperature independent, signaling a breakdown of the phonon-gas model, attributed to phonon localization and wave-like coherence, modeled using the linearized Wigner transport equation (LWTE). The phonon localization in the 0D crystal structure results in a crossover from populations conductivity ( κ p ) associated with particle-like phonon propagation to coherence conductivity ( κ c ) through wave-like tunneling, at 175 K. Our study reveals 0D structural confinement along with anharmonic local structural dynamics can enable particle-to-wave-like phonon crossover, establishing a pathway to mixed phononic regimes and suppressed thermal transport.